DNA-methyltransferase1 (DNMT1) binding to CpG rich GABAergic and BDNF promoters is increased in the brain of schizophrenia and bipolar disorder patients - Dong, E. (Schizophr Res, 2014)
The down regulation of glutamic acid decarboxylase67 (GAD1), reelin (RELN), and BDNF expression in brain of schizophrenia (SZ) and bipolar (BP) disorder patients is associated with overexpression of DNA methyltransferase1 (DNMT1) and ten-eleven translocase methylcytosine dioxygenase1 (TET1). DNMT1 and TET1 belong to families of enzymes that methylate and hydroxymethylate cytosines located proximal to and within cytosine phosphodiester guanine (CpG) islands of many gene promoters, respectively. Altered promoter methylation may be one mechanism underlying the down-regulation of GABAergic and glutamatergic gene expression. However, recent reports suggest that both DNMT1 and TET1 directly bind to unmethylated CpG rich promoters through their respective Zinc Finger (ZF-CXXC) domains. We report here, that the binding of DNMT1 to GABAergic (GAD1, RELN) and glutamatergic (BDNF-IX) promoters is increased in SZ and BP disorder patients and this increase does not necessarily correlate with enrichment in promoter methylation. The increased DNMT1 binding to these promoter regions is detected in the cortex but not in the cerebellum of SZ and BP disorder patients, suggesting a brain region and neuron specific dependent mechanism. Increased binding of DNMT1 positively correlates with increased expression of DNMT1 and with increased binding of MBD2. In contrast, the binding of TET1 to RELN, GAD1 and BDNF-IX promoters failed to change. These data are consistent with the hypothesis that the down-regulation of specific GABAergic and glutamatergic genes in SZ and BP disorder patients may be mediated, at least in part, by a brain region specific and neuronal-activity dependent DNMT1 action that is likely independent of its DNA methylation activity.